Categorization and complication of non-alcoholic fatty liver disease - Alharbi, Samar A.; Alhayki, Ammar H.; Alghamdi, Ahmed A.; Althobaiti, Abdulrahman S.; Alkhalfan, Fatema F.; Muaddi, Nawaf A.; Almabouth, Mohammad S.; Alfaraj, Zainab M.; Almajed, Mohammed H.; Alkhiri, Ali A.; Altharmani, Basmah A. (International Journal Of Community Medicine And Public Health, 2022)
Non-alcoholic fatty liver disease is the most prevalent liver disease with a global prevalence of 25%. The frequency of non-alcoholic fatty liver disease and the percentage of people with severe liver disease are expected to rise given the ongoing obesity pandemic, the rise in diabetes, and other factors. This will have a significant effect on health care expenditure and the need for liver transplantation, for which non-alcoholic steatohepatitis is already on track to overtake alcoholic steatohepatitis as the most prevalent reason. Non-alcoholic fatty liver disease is characterized by the triglyceride accumulation in the cytoplasm of hepatocytes. Patients with non-alcoholic fatty liver disease who have advanced fibrosis and non-alcoholic steatohepatitis are at much higher risk of negative outcomes, such as overall mortality and liver-specific morbidity and death. It is a multisystemic clinical illness entity that manifests extrahepatic conditions like polycystic ovarian syndrome, type 2 diabetes, chronic renal disease, hypothyroidism, and psoriasis. In fact, cardiovascular disease, cancer, and liver-related problems are the three leading causes of death in non-alcoholic fatty liver disease patients, in that order. Non-alcoholic fatty liver disease is further divided into two subtypes hepatic steatosis and non-alcoholic steatohepatitis ranging from milder to more aggressive form of the disease.